A comparison of adjuvant therapy modality and treatment outcomes between appalachian and non-appalachian patients with high-risk endometrial carcinoma - Josie D. Llanora; Gregory S. Hawk; Laura M. Harbin; Sara Lee; Madison Lane; Madison T. Hickey; Elizabeth Pendygraft; Lauren A. Baldwin; Megan L. Hutchcraft (Gynecologic Oncology Reports)
Objective: The incidence and mortality of endometrial cancer is increasing. After surgical staging, patients with high-risk disease often undergo adjuvant treatment, which may include systemic therapy, radiation therapy, or combined modalities. Patients in rural Appalachia have limited access to subspecialty care needed for optimal disease management. This study aims to compare adjuvant treatment regimens and outcomes among patients with high-risk endometrial cancer living in Appalachian and non-Appalachian regions. Methods: We retrospectively identified 179 patients with high-risk endometrial carcinoma who underwent surgical staging at a single academic medical center and received adjuvant therapy between 2012 and 2019. Patients were identified as Appalachian (n = 119) and non-Appalachian (n = 60) residents based on home ZIP code. Adjuvant therapy regimen, recurrence rate, recurrence location, progression free survival (PFS), and overall survival (OS) were compared. Statistical comparisons were performed using multinomial and ordinal logistic regression models, Kaplan-Meier curves, Log Rank test, two-sample t-tests, Fisher’s exact, and chi-square tests. Results: There was no significant difference in adjuvant therapy regimen between groups. Overall recurrence rates were similar, though rate of vaginal recurrence was higher among non-Appalachian patients compared to Appalachian patients (42 % vs. 14 %, p = 0.05). There were no differences in rate of pelvic or distant recurrences, PFS, or OS. Conclusion: Despite lower densities of subspecialists in rural Appalachia, Appalachian and non-Appalachian patients with high-risk endometrial cancer received similar adjuvant therapy regimens and had similar disease outcomes. Further efforts should work to optimize treatment and surveillance for patients with endometrial carcinoma with barriers to subspecialty care.